Liberdade e má-fé em Sartre: matizes ético-fenomenológicos - Picinini, Cristiane (2018)
The present dissertation aims to investigate the phenomenon of freedom and bad faith, in the light of the existentialist work of Sartre under an ethical-phenomenological nuance. To this end, the work reconstitutes the conceptions of Descartes and Leibniz as classic paradigms of the idea of freedom founded on substantialist presuppositions. We then proceed to the conceptualization of correlates of bad faith, because to speak of this phenomenon, we have to trace a path that runs through the ideas of contingency, anguish, engagement, project, and moral problems as to the effective choice of a project that is faced with the world, and needs determinations. Our great concern here is to show the reader that bad faith is the inauthenticity of a Being, who escapes from anguish, and therefore from freedom. We will show that the concept, far from representing a simple Sartrian moralism, puts in a radical way the propensity for substance, of the which runs through the nothingness of for-you, and constitutes the freedom (lack of being) that constitutively distresses and launches in the project. It is, as we are trying to show, of nonconformity within the being of the Self, which is conjugated to the discovery of the Others, in the measure in which a struggle for recognition — struggle for being is established. It is a mistake that it is a lie to oneself. In order to better illustrate this phenomenon of error and deception proper to the human condition, we make use of some examples present in The being and the Nothing, besides an analysis of cases, that we turn to the literature of Fiódor Dostoiévski. It is in the analysis of the central characters of the works Memories of the Underground and Crime and Punishment, which we describe, therefore, how are these are figures of bad faith.